Application of nuclear energy for environmentally friendly hydrogen generation - Yamawaki, Michio; Nishihara, Tetsuo; Inagaki, Yoshiyuki; Minato, Kazuo; Oigawa, Hiroyuki; Onuki, Kaoru; Hino, Ryutaro; Ogawa, Masuro (International Journal of Hydrogen Energy, 2007)
It is universally admitted that hydrogen is one of the best energy media and its demand will increase greatly in the near future. However, little hydrogen exists naturally, so that how to generate hydrogen without bringing forth much CO 2 will be very important research subject. Hydrogen generation from water using nuclear energy is one of the solutions for this problem. Especially, the high temperature gas cooled reactor (HTGR) has a possibility to generate hydrogen economically compared with other types of nuclear reactors. As for long-lived radioactive waste to be generated by nuclear reactors, it is expected to significantly reduce its burden to the human environment by applying transmutation technologies. This report describes the feature of the hydrogen generation with HTGR and the development of the accelerator-driven subcritical system to reduce radioactive waste ongoing at JAEA.